1.1.2 Enzyme Classification and Nomenclature and Biocatalytic Retrosynthesis - Liese,A.; Pesci,L. (Biocatalysis in Organic Synthesis 1, 2015)
The enzyme nomenclature system is based on six different enzyme classes, defined by the type of chemical reaction catalyzed; hence, for a given synthetic step, it is possible to plan an enzymatic transformation (even thinking in a retrosynthetic manner) for the synthesis and/or modification of a certain compound. With this premise, the possibility of combining the methods of traditional chemical retrosynthesis with biocatalytic transformations provides an enormous potential benefit for organic chemists, including the use of modern feedstocks and “sustainable chemistry” criteria. In this chapter, enzyme nomenclature is discussed, and the related information is used as a basis for applying biocatalytic retrosynthetic analysis to several classes of organic molecules. Some key examples are provided in order to appreciate the real potential of biocatalytic retrosynthesis, especially when used in combination with more traditional chemical strategies.
Keywords: Referencework; enzyme nomenclature; reaction types; organic synthesis; retrosynthesis; green chemistry